Traınıng on Basıc Busıness Skılls Needed in Internatıonalısatıon For Vıetnamese Small and Medıum-Sızed Enterprıses - Le Tien Dat; Suku Sukunesan; Christopher Selvarajah (Department of Management, Faculty of Economics and Business, Brawijaya University, 2018)
Small and medium – sized enterprises (SMEs) are often considered the primary source of economic development and integration in developing countries, including Vietnam. However, in the process of transitioning from a controlled economy to a market-oriented economy, many Vietnamese SME managers still lack basic business skills to compete successfully in international markets. Comprehensive training programs on basic business skills, therefore, should be developed to improve the capacity of Vietnamese SME managers. This paper aims to identify the training needs and appropriate training programs to raise these skills. Fifty-eight SME managers from three major cities of Vietnam (Hanoi, Da Nang and Ho Chi Minh City) participated in twelve focus groups with each group being between three and eight members. Participants from these SMEs were grouped either as managers presenting potential exporters or current exporters. It can be seen from the findings that two groups of SMEs emphasized a series of categories of basic business skills, namely marketing skills, production skills, management skills, financial skills, and IT skills. Nonetheless, there were noticeable differences between the two groups about specific skills. Based on the perceptions of Vietnamese SME potential exporters and current exporters with regard to basic business skills needed in exporting activities, recommendations about training programs are provided. With regard to some skills, common training programs may be provided to both groups of managers, whereas, with other skills, separate training programs for each group of managers may be more appropriate and effective. For instance, the introduction to basic knowledge about international marketing, and skills to develop products which are able to be exported should be included in the training programs for SME potential exporters. Meanwhile, the training including promotion skills, especially skills to promote brands in international markets, and guidance on managing in-put materials, particularly selecting suppliers and maintaining the quality of in-put materials to meet the requirements of foreign partners should be arranged for the current exporters only. The outcomes of this study are expected to be useful for not only SME managers, but also training organisations and government associations in designing and developing training programs. The study also adds to the body of knowledge covering human resource development in developing countries.